Effects of increased elderly employment on other workers' employment and elderly's earnings in Japan - Ayako Kondo (IZA Journal of Labor Policy, 2016)
This paper examines the effect of increased elderly employment in Japan, caused by the legal obligation of continued employment enacted in 2006, on employment of other workers and elderly's own earnings. I find no evidence for substitution between young full-time workers and elderly workers, while there might be a modest crowd out of middle-aged female part-time workers. I also find a substantial decline in earnings of baby boomers, who reached age 60 after 2006, in their early sixties. These results suggest that firms primarily cut wages of elderly workers, and some firms reduced the number of female part-time workers.
Keywords: J26; 330; Elderly employment; Youth employment